Population Dynamics of Sorghum Foliage-feeding Insects and their Natural Enemies in Relation to Abiotic Factors - Thilak, K. S.; Panickar, Bindu; Chandaragi, M. K.; Balraj, G.; Bhanavathu, S.; Joshi, V. J. (International Journal of Bio-resource and Stress Management, 2026)
A field investigation was carried out during the summer (March–June), kharif (July–September) and rabi (November–February) seasons of 2024–25 at the Agronomy Instructional Farm, Sardarkrushinagar, to study the population dynamics of foliage-feeding insect pests and their natural enemies in relation to abiotic factors. The study revealed distinct seasonal variations in pest and natural enemy activity. During the summer season, ash weevil and leaf hopper populations reached their peak during the 18th and 21st Standard Meteorological Week (SMW), respectively, while spider activity was highest during the 19th SMW. In the kharif season, major pests such as ash weevil, leaf folder and aphid, along with the natural enemy coccinellids, recorded peak incidence between the 33rd and 35th SMW. During the rabi season, aphid population attained its maximum between the 48th SMW and 1st SMW, indicating its dominance during cooler months. Correlation analysis showed that abiotic factors such as bright sunshine hours, temperature and relative humidity significantly influenced the population build-up of insect pests and their natural enemies, although the degree and direction of influence varied across seasons. Regression analysis further indicated that abiotic factors had a strong influence on pest incidence during the kharif season (R²= 0.75–0.94), a moderate influence during rabi (R²=0.64–0.79), and a comparatively lower influence during summer (R²=0.28–0.67). Overall, the findings emphasized the crucial role of weather parameters in regulating seasonal pest occurrence and natural enemy activity, which could support the development of timely, season-specific and location-based pest management strategies.